Antioxidant Effect of Vitamins in Olive Oil Emulsion - Cuomo, Francesca; Cinelli, Giuseppe; Chirascu, Catalina; Marconi, Emanuele; Lopez, Francesco (Colloids and interfaces, 2020)
In this study, water-in-extra virgin olive oil emulsions were enriched with vitamins. Water-in oil emulsions are heterogeneous systems able to solubilize both hydrophilic and hydrophobic compounds. Thus, hydrophilic vitamin C and lipophilic vitamin E were loaded separately or together in emulsion. A suitable emulsion composition was selected after considering different surfactant (mono and diglycerides of fatty acids, E471; sorbitan monooleate, Span 80; polyoxyethylene sorbitan monooleate, Tween 80) and water concentrations. The most appropriate emulsion, for the high stability, resulted the one containing concentrations of Span 80 1% w/w and water 1% w/w. The antioxidant effect of vitamins in emulsions was studied considering the variation of the peroxide values during storage. The oxidation reaction was slowed down in emulsions containing vitamin C, but it was quickened by the loading of vitamin E for its high concentration. In emulsions containing vitamin E, indeed, the peroxide values were higher than in emulsions prepared in the absence of vitamins or in oil. The antioxidant activity generated by the co-loading of vitamin C and E was very effective to the point that in presence of high amounts of vitamins the peroxide values did not change in about 40 days of storage, due to the vitamin E regeneration by vitamin C.